Tolerancia experimental de las especies vegetales Nicotiana glauca, Jacaranda mimosifolia, Tecoma stans, Medicago sativa y Spinacea oleracea al boro, en Argentina - L. de Viana, Marta (2008)
The activity of boron industries is a punctual and diffuse source of air, soil and water pollution. Therefore, it is a priority to study possible ways of reducing this impact. A relatively new technology for reducing soil pollution is phytoremediation, which uses plants and associate microorganisms. The first step in phytoremediation is to detect tolerant plant species, which is the objective of this work. A laboratory experiment to assess the germination, survival and growth of different spe-cies at different boron concentrations was carried out following a factorial design with two factors: plant species and boron concentration. Boron concentrations were determined at the beginning and the end of the experiment, taking into account substrates with and without vegetation. We found significant differences for treatment, species and the interaction species*treatment. N. glauca, M. sativa and J. mimosifolia were the most tolerant species. The other species had a decrease in the response variables, with the concentration of the pollutant. All the species had a low survival at the highest boron concentration. The reduction in boron concentration at the end of the experiment was higher in the 30 ppm treatment with M. sativa and the lower was registered in the 20 ppm treatment with J. mimosifolia and in 30 ppm with T. stans and S. oleraceae. We conclude that N. glauca, M. sativa and J. mimosifolia can be considered in remediation plans.